Physiological test of Lactobacillus sp. Mar 8 probiotic which encapsulated by using spray dryer to reduce cholesterol - TITIN YULINERY; EKO YULIANTO; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
The research on physiology test of Lactobacillus sp. Mar 8 probiotic which encapsulated by using spray dryer to reduce cholesterol has been conducted. The aim of the research was to know the influence of encapsulation process on the Lactobacillus cells to its activities on binding cholesterol, the ability to grow of the bacteria on lower pH 1-6 and the growth on Na-taurocholate at 17 mM concentration. The Emulator used was skimmed milk with 5% and 10% in concentration. The result showed that the bacteria used skimmed milk with 10% concentration was remain stable in growing ability such as growing on GYP medium in lower pH (1-6), growing on sodium taurocholate in 17 mM concentration, and the ability on binding cholesterol. So, encapsulated Lactobacillus can be used as probiotic agent to reduce cholesterol. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: probiotik, Lactobacillus sp. Mar 8, encapsulation.